2014
DOI: 10.1186/1472-6831-14-103
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of oral squamous cell carcinoma in Northern Norway: a retrospective study

Abstract: BackgroundThe main aim of the study was to evaluate if patients with oral squamous carcinomas in Northern Norway differ from patients in other countries with regard to clinicopathological characteristics and also study the influence of risk factors. Such a comparison is of demographical interest, and also important for the interpretation of result from studies on prognostic biomarkers.MethodsWe describe clinicopathological characteristics of 133 North Norwegian patients diagnosed with squamous cell carcinoma o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 35 publications
7
36
0
2
Order By: Relevance
“…[13] There has been strong correlation with tobacco usage in various forms. [18][19][20] Buccal mucosa belongs to the gingivobuccal complex of which lower gingivobuccal complex is known as Indian cancer. This is the typical site associated with tobacco chewing.…”
Section: Discussionmentioning
confidence: 99%
“…[13] There has been strong correlation with tobacco usage in various forms. [18][19][20] Buccal mucosa belongs to the gingivobuccal complex of which lower gingivobuccal complex is known as Indian cancer. This is the typical site associated with tobacco chewing.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown no relationship between these factors, including Rikardsen. (8) In contrast, Ribeiro (9) claimed that older patients had a worse prognosis for OSCC and Dohlstom (23) who found that younger patients with more invasive OSCC had a worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…(5) Despite the advances in therapeutics and diagnosis, the overall prognosis of OSCC remains unfavorable, with 30% recurrence rates from local or regional disease, 25% for distal metastases, and a 40% 5-year survival rate. (6) The association between the OSCC prognosis and age and sex is controversial, as some studies have not shown such a relationship, (7,8) whereas others have revealed that the prognosis of OSCC is worse in older aged men. (9,10) No relationship between prognosis and smoking and alcohol use was reported in one study, (7) whereas another reported higher mortality rates in cigarette smokers and alcohol drinkers.…”
mentioning
confidence: 99%
“…Treatment planning today is based largely on tumor size and the presence and pattern of lymph node invasion [7072]. Small tumors without lymph node invasion are treated typically with just surgery while small tumors with lymph node invasion and all large tumors are treated with surgery plus radiation and/or chemotherapy [73].…”
Section: Prognosis Of Oscc Based On Mirnas In Surgically Obtained Tissuementioning
confidence: 99%